Factors asociated with breastfeeding practices among mothers of 0-6 month-old infants in Jos North Lga, Plateau State, Nigeria - Itse, Jacdonmi (2016)
Background: Exclusive breastfeeding practice (EBF) is a safe and simple intervention in improving child health and growth. However the practice of EBF is still low especially in developing countries despite an increase in awareness and understanding of exclusive breastfeeding. Exclusive breastfeeding has been identified to be the most significant and effective child survival strategy and accounts for 15 % of preventable infant deaths. Early introduction of breast milk and exclusive breastfeeding has been found to be quite low, with percentages of 38 % and 17 % only respectively in Nigeria. Objective: To determine infant feeding practices, factors associated with breastfeeding practices among mothers and determine the nutritional status of infants 0-6 months in Jos North LGA, Nigeria. Methodology: This was a cross-sectional study. Data was collected from 310 motherinfant pairs giving an overall response rate of 96.3 %. A multistage sampling was employed. Three primary health care facilities in Jos North LGA were randomly selected, simple random sampling probability proportionate to size was carried out to calculate number of respondents from each health facility, and afterwards, a computer generated table of random numbers was employed to select mothers using the sampling frame which was made from the immunization register at the health facilities. Data collection consisted of two parts. A validated questionnaire was administered to mothers. The questionnaire consisted of questions relating to socio-demographic characteristics, breastfeeding and also weaning practices. Anthropometric measurements (weight and length of infants) were taken. Main outcome measures were factors associated with breastfeeding practice, nutritional indices in terms of stunting, underweight and wasting of infants. Data analysis was performed using SPSS 22 and Epi Info 2007. All results were significant at alpha value ≤0.05. Results: All mothers (100 %) were still breastfeeding at the time of data collection. However, only 39.7 % were seen to practice exclusive breastfeeding. About 33 % of infants had already been introduced to complementary foods even before the age of 6 months. In multivariate logistic regression, maternal and related factors associated with EBF included mothers perceived insufficient breast milk supply (AOR=0.194; 95 % CI: 0.074-0.509), mothers ability to express (AOR=10.697; 95 % CI: 4.578-24.993), EBF duration understanding, 0-1 months (AOR= 0.225; 95 % CI: 0.079-0.641) and time at which breastfeeding was initiated immediately after birth (AOR=2.732; 95 % CI: 1.455-5.128). Mother’s socio-demographic predictors of EBF included ethnicity and marital status. In terms of prevalence of malnutrition among males, 13.2 % were severely stunted, 1.6 % were severely underweight and 6.5 % were wasted. Among females, 8.4 % were severely stunted, 0.6 % were severely underweight and 6.6 % were severely wasted. There was a significant difference in nutritional indices and breastfeeding patterns (p<0.05). Conclusion: Exclusive breastfeeding rates are still low and does not conform to the guidelines and recommendations on appropriate infant feeding by WHO and UNICEF. Factors associated with the breastfeeding practices are mother’s ethnicity, marital status, perception of insufficient breast milk production, ability to express breast milk, understanding of exclusive breastfeeding duration and the time at which a mother initiated breastfeeding. These study’s findings should serve as baseline for exclusive breastfeeding interventional studies and programs.